RESULTS OF CARE FOR PATIENTS WITH ARTHRITIS AND SOME RELATED FACTORS AT HUU NGHI HOSPITAL IN 2021 (Vietnam Journal of Community Medicine, 2022)
Objectives: (1) Describe the results of care for arthritis patients at Friendship hospital. (2) Analysisof some factors related to care’s results.Methods: A prospective descriptive study was carried out from June 2021 to December 2021 on 125arthritis patients inpatient treatment at Huu Nghi Hospital.Results: The most common clinical symptom was joint pain (96%); limited joint mobility (89.6%);morning stiffness (28.8%); 15.2% joint deformity. The percentage of patients receiving massage,exercise, lighting, mental health care, nutrition care, and sleeping care on the first day, the third dayand the fifth day reached over 50.4%. These rates were higher than those at the time of admission.The percentage of patients receiving health counseling and education during were over 68.8%. Theproportion of good care was 78.4%; moderate care was 21.6%. Factors related to the care’s results ofpatients with arthritis include age, BMI, nutritional education and personal hygiene education.Conclusions: The rate of good care was 78.4%; moderate care was 21.6%. Factors related to thecare of patients with arthritis include age, BMI, disease duration, nutritional and personal hygieneeducation with OR 3.30 (1.15-9,43). 43); 2.74 (1.14-6.56); 3.28 (1.29-8.29); 3.28 (1.29-8.29); 4.13(1.66-10.27).
Keywords: Arthritis, care results, the patients.